2019
DOI: 10.13165/vpa-19-18-2-05
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this article is to propose the integrated index of Public Governance efficiency based on the Fishburne's method, considering the impact's power and direction of the different sub-indexes (Worldwide Government Indicators) on macroeconomic stability and eliminating the issue of multicollinearity. The object of the study was 11 European countries that had two common features: 1) in the political sphere, during 1990-1992 the countries started the political transformation process by refusing the mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…This cluster could be called «public administration». http://mmi.fem.sumdu.edu.ua/en The findings proved that scientific community around the world analysed the public administration and innovations from the different points of views: social and economic development of the national economy (Bilan et al, 2019e;Vasylieva et al, 2017bVasylieva et al, , 2013;Dalevska et al, 2019;); the influence of bank and financial system on innovation development (Bilan et al, 2019a;Buriak et al, 2015;Vasylieva et al, 2017a;Bilan et al, 2019d;Kaźmierczyk and Chinalska, 2018;Tkachenko et al, 2019b;Brychko et al, 2018); country's brand management (Bilan et al, 2019b); macroeconomic stability (Bilan et al, 2019c;Dementyev and Scherbakov, 2017); green innovations and energy policy (Yevdokimov et al, 2018;Pimonenko et al, 2017;Chygryn et al, 2019;Pająk et al, 2017); new management trends .…”
Section: Figure 1 Publication Activity In Scopus On Innovations and mentioning
confidence: 83%
“…This cluster could be called «public administration». http://mmi.fem.sumdu.edu.ua/en The findings proved that scientific community around the world analysed the public administration and innovations from the different points of views: social and economic development of the national economy (Bilan et al, 2019e;Vasylieva et al, 2017bVasylieva et al, , 2013;Dalevska et al, 2019;); the influence of bank and financial system on innovation development (Bilan et al, 2019a;Buriak et al, 2015;Vasylieva et al, 2017a;Bilan et al, 2019d;Kaźmierczyk and Chinalska, 2018;Tkachenko et al, 2019b;Brychko et al, 2018); country's brand management (Bilan et al, 2019b); macroeconomic stability (Bilan et al, 2019c;Dementyev and Scherbakov, 2017); green innovations and energy policy (Yevdokimov et al, 2018;Pimonenko et al, 2017;Chygryn et al, 2019;Pająk et al, 2017); new management trends .…”
Section: Figure 1 Publication Activity In Scopus On Innovations and mentioning
confidence: 83%
“…Some of them are correlated with each other. Thus, Bilan et al (2019) proposed the approach to integrate WGI index based on the Fishburne's method, considering the impact's power and direction of the different subindexes WGI on FDI inflow and eliminating the issue of multicollinearity. To calculate, it is suggested to use the formula:…”
Section: Methodsmentioning
confidence: 99%
“…The results of the generalisation of scientific research showed that researchers analysed a different set of factors influencing the transformation processes of the transition to a climate-free economy. Thus, scientists have identified social (Palienko et al, 2017;, ecological Mačaitytė et al, 2018); Matsenko et al, 2017), economic (Bhowmik, 2019;Bilan et al, 2019) determinants of the impact on macroeconomic stability in reforming the energy sector in the direction of carbon neutrality.…”
Section: Literature Reviewmentioning
confidence: 99%